2003
DOI: 10.1002/ana.10610
|View full text |Cite
|
Sign up to set email alerts
|

Impaired sequence learning in carriers of the DYT1 dystonia mutation

Abstract: Previous positron emission tomography (PET) studies have shown that nonmanifesting carriers of the DYT1 dystonia mutation express an abnormal pattern of resting glucose metabolism. To determine whether motor behavior is impaired in these subjects, we compared movement and sequence learning in 12 clinically unaffected DYT1 carriers with 12 age-matched controls. Regional differences in brain function during task performance were assessed with simultaneous H 2 15 O/PET. We found that motor performance was similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
147
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 186 publications
(158 citation statements)
references
References 33 publications
9
147
0
1
Order By: Relevance
“…General features of the motor tasks have been detailed previously [16,17]. Briefly, subjects moved a cursor on a digitizing tablet with their right hand out and back from a central starting point to one of eight radially arrayed targets at 1.6 cm distance.…”
Section: Motor Tasksmentioning
confidence: 99%
See 2 more Smart Citations
“…General features of the motor tasks have been detailed previously [16,17]. Briefly, subjects moved a cursor on a digitizing tablet with their right hand out and back from a central starting point to one of eight radially arrayed targets at 1.6 cm distance.…”
Section: Motor Tasksmentioning
confidence: 99%
“…We use tasks where subjects are explicitly asked to learn and anticipate the order of appearance of eight targets. We have previously shown that, with these tasks, normal subjects typically learn the order of simple repeating sequences in ninety seconds or less, either when learning occurs while reaching for targets or when, in a less demanding situation, the sequence order is first learned visually, without moving [16][17][18]. Learning of the sequence order is reflected by decreases of onset time, as subjects move out of reaction-time mode and anticipate target appearance, and measured with discrete variables, such as the number of correct anticipatory movements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Whereas this characteristic pattern was initially identified in affected PTD patients, 106 its presence was subsequently confirmed in genotyped subjects, even without clinical manifestations. 38,39,107 Further studies revealed subtle behavioral impairments in nonmanifesting DYT1 carriers, 108 as well as abnormalities in brain activation responses during movement and nonmotor learning. It is therefore possible that TDRP expression can represent an endophenotype for dystonia, which may be useful in gene identification in at risk populations (FIG.…”
Section: Torsion Dystoniamentioning
confidence: 99%
“…Theoretically, this cerebellar abnormality could be primary or secondary to dysfunction of the basal ganglia. However, in DYT1 carriers, functional imaging suggests the primary dysfunction of the basal ganglia leads to compensatory maladaptive neural output from the cerebellum (Ghilardi et al, 2003;Carbon et al, 2008b).…”
Section: Discussionmentioning
confidence: 99%